PENGARUH YOUTUBER GADGET REVIEW, WORD OF MOUTH, DAN PRODUCT FEATURES TERHADAP MINAT MEMBELI PRODUK SMARTPHONE MERK SAMSUNG DI INDONESIA - Robbani Afdhalul Ikhsan; Rusminah HS; Muh. Mujahid Dakwah (Master of Management, Mataram University, 2020)
This study used an associative quantitative method that measured the effect of independent variables on the dependent variable. The purpose of this research was to determine the significance of the gadget reviews by YouTubers, word of mouth, and product features on the buyers’ interest in Samsung smartphone product. The method used in this study was non-probability sampling method which used the purposive sampling technique. The data were obtained through a questionnaire in the form of google form which was distributed to 100 people. The result showed that; the gadget reviews by YouTubers had no effect on the buyers’ interest where the significance level was 0,068, word of mouth had an effect on the buyers’ interest and it was significant where the significance level was 0,019, and product features also had a significant effect on the buyers’ interest where the significance level was 0,001.Keywords :Gadget Reviews by Youtubers, Word of Mouth, Product Features, Buying Interest